A polymerizable liquid crystal composition and display device thereof

By using polymerizable liquid crystal compositions with specific structural compounds, the controllable polymerization after UV light irradiation, the problems of unstable pretilt angle and long response time in PSVA liquid crystal display are solved, and long-term stability under different temperature conditions are achieved and low residual properties.

CN116904209BActive Publication Date: 2025-02-18CHONGQING HALATION SEIKO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310683366.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2025-02-18
Estimated Expiration
2043-06-09

AI Technical Summary

Technical Problem

After UV light exposure, existing PSVA liquid crystal displays have too much polymerizable monomer residues in the liquid crystal mixture, resulting in unstable pretilt angle, long response time, and inconsistent performance under high and low temperature conditions.

Method used

A polymerizable liquid crystal composition containing specific structural compounds is adopted, which polymerizes controllably during UV light irradiation to form a stable pretilt angle and remains stable for a long time under high and low temperature conditions while reducing polymerization Residue of monomer.

Benefits of technology

The uniformity and stability of the pretilt angle after UV light irradiation is achieved, the response time is reduced, and good performance is maintained under different temperature conditions, reducing the residue of polymerizable monomers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116904209B_ABST
    Figure CN116904209B_ABST
Patent Text Reader

Abstract

The present invention relates to a polymerizable liquid crystal composition and a display device thereof, and belongs to the field of liquid crystal materials. The polymerizable liquid crystal composition comprises at least one compound having a structure shown in general formula I: at least one compound shown in general formula P: at least one compound shown in general formula II: at least one compound shown in general formula III: and at least one compound shown in general formula M, wherein compound M is selected from compounds represented by general formula M-I and / or M-II: The liquid crystal composition of the present invention has very low rotational viscosity, good phase performance and good low-temperature performance, and can form a lower pretilt angle after UV irradiation, has less RM residue, lower threshold voltage and faster response time, and the formed pretilt angle has long-term stability under high and low temperature conditions, and can meet the requirements of liquid crystal display devices for low power consumption and good display effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a liquid crystal composition and application thereof, in particular to a negative polymerizable liquid crystal composition and a display device thereof, belonging to the field of liquid crystal materials. Background Art

[0002] Liquid crystal mixtures are widely used in various liquid crystal display devices due to their refractive index anisotropy, dielectric anisotropy and other characteristics. Among them, VA (vertical alignment) liquid crystals have attracted much attention due to their good viewing angle, contrast and other characteristics, but VA liquid crystal displays also have certain disadvantages, especially the common problem of slow response time. In recent years, a series of VA technologies have been continuously developed, including MVA, PVA, PSVA and other technologies.

[0003] Among them, the PSVA (polymer stabilized vertical alignment) display technology is to add a certain amount of polymerizable liquid crystal compound (RM) to the nematic liquid crystal host, then fill the liquid crystal between two glass substrates with electrodes, apply a certain voltage, and the liquid crystal molecules rotate under the action of the electric field to form a certain initial pre-tilt angle, and then after irradiation with ultraviolet light of a certain energy, the polymerizable monomers therein are polymerized to form a cross-linked network, and the applied voltage is removed, and the formed pre-tilt angle is maintained due to the cross-linked network. In actual processes, not all polymerizable monomers and liquid crystal hosts are suitable for PSVA technology. In the prior art, after the mixed liquid crystal is irradiated with UV light, some polymerizable monomers will remain. During the image display process, it is triggered by the environment or backlight and uncontrolled polymerization occurs, resulting in a change in the pre-tilt angle of the region. During the process of switching the screen of the liquid crystal display, the transmittance of the region changes unexpectedly, resulting in the occurrence of afterimages. Another problem that has been observed in the use of PSVA displays is the stability of the pre-tilt angle. The reason is that the pretilt angle generated by the polymerized RM during display manufacturing cannot remain constant after a long period of charge and discharge operation. As a result, the pretilt angle of the LCD will change, thereby reducing the performance of the LCD.

[0004] Therefore, a liquid crystal composition having the following characteristics is particularly desired: during UV light irradiation, the RM polymerization in the liquid crystal mixture is controllable, the pretilt angle formed is uniform and can be stably maintained for a long time under high and low temperature conditions, and the RM residue after polymerization is as small as possible. In addition, this type of liquid crystal composition must have a lower rotational viscosity to achieve the purpose of reducing the response time. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention discloses a polymerizable liquid crystal composition, which has the characteristics of less RM residue, stable pretilt angle formed, and low rotational viscosity. When used as a liquid crystal material, it can shorten the response time and improve the performance of liquid crystal displays.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A polymerizable liquid crystal composition, comprising: at least one compound of the structure shown in general formula I as a first component:

[0008]

[0009] Among them, R A1 , R A2 Each independently represents an alkyl group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms;

[0010] L1 and L2 each independently represent H or -CH3;

[0011] Z1 represents a CC single bond, -CH2O- or -OCH2-;

[0012] a represents 0 or 1; b represents 1 or 2;

[0013] At least one compound represented by the general formula P is used as the second component:

[0014]

[0015] Among them, rings B1, B2, and B3 are independent of each other. in One or more H on the molecule can be replaced by -F, -Cl, or -OCH3;

[0016] Z4 and Z5 each independently represent a CC single bond, -CH2CH2-, -CH=CH-, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CO-O-, -C2F4-, or -CF=CF-;

[0017] P1 and P2 each independently represent a polymerizable group; the polymerizable group is a methacrylate group or an acrylate group;

[0018] Sp1 and Sp2 each independently represent a spacer group or a CC single bond; the spacer group is a straight or branched alkyl chain group of 1 to 6 carbon atoms;

[0019] r and s each independently represent an integer from 0 to 4;

[0020] At least one compound of general formula II is used as the third component:

[0021]

[0022] Among them, R C1 , R C2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms;

[0023] Rings C1, C2, and C3 are each independently low At least one of and At most one H on can be replaced by F;

[0024] c represents 0, 1, 2. When c represents 2, the ring C2 may be the same or different; d represents 0 or 1;

[0025] At least one compound represented by the general formula III is used as the fourth component:

[0026]

[0027] Where R D1 , R D2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms;

[0028] and one or more compounds represented by the general formula M as the fifth component, the compound M is selected from the compounds represented by the following general formulas MI and / or M-II:

[0029]

[0030] Among them, R M1 , R M2 Each independently represents an alkyl group of 1 to 12 carbon atoms or an alkoxy group of 1 to 12 carbon atoms; rings M1 and M2 each independently represent

[0031] In the liquid crystal composition, calculated by mass percentage, the content of the compound represented by general formula I is 1-50%, the content of the compound represented by general formula P is 0.001-5%, the content of the compound represented by general formula II is 1-50%, the content of the compound represented by general formula III is 1-50%, and the weight percentage of the compound represented by general formula M is 1%-70%.

[0032] Furthermore, the liquid crystal compound represented by the general formula I is preferably a compound represented by the following structural formulas IA to IJ:

[0033]

[0034] Among them, R A1 It represents an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkenyloxy group having 2 to 5 carbon atoms.

[0035] Furthermore, the compound represented by the general formula I is selected from at least one compound represented by the general formula IA, and at least one compound represented by the general formula IB, IC, IF and / or IH.

[0036] Further, Formula I can be selected from at least one compound of Formula IA and at least one compound of Formula IB;

[0037] Further, Formula I can be selected from at least one compound of Formula IA and at least one compound of Formula IC;

[0038] Further, Formula I can be selected from at least one compound of Formula IA and at least one compound of Formula IH;

[0039] Furthermore, the compound of formula I can be selected from at least one compound of formula IA and at least one compound of formula IF.

[0040] In some embodiments of the present invention, preferably, the compound represented by the general formula I is selected from one or more of the following groups consisting of compounds I-1 to I-64:

[0041]

[0042]

[0043]

[0044]

[0045] Relative to the total weight of the liquid crystal composition of the present invention, the weight percentage of the compound represented by general formula I is 1%-50%, preferably 1%-48%, 1%-45%, 1%-40%, 2%-50%, 2%-48%, 2%-45%, etc.; relative to the total weight of the liquid crystal composition of the present invention, the lower limit of the weight percentage of the compound represented by general formula I is 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 20%, 22%, 24% or 26%; the upper limit of the weight percentage of the compound represented by general formula I is 50%, 48%, 45%, 40%, 38%, 35%, 30%, 28%, 26%, 24%, 20%, 18%, 16%, 15%, 14%, 12% or 10%.

[0046] Preferably, the compound represented by the general formula P is selected from one or more of the following compounds PA to PK:

[0047]

[0048]

[0049] Wherein, P1 and P2 have the same meanings as in the general formula P, and Sp has the same meaning as Sp1 and Sp2.

[0050] Furthermore, the compound of the general formula P is selected from a combination of compounds represented by any two or more of the general formulae PA, PB, PD, PF and PG.

[0051] Furthermore, the compound of general formula P is selected from at least one compound represented by general formula PA, PB, PD and / or PG, and at least one compound represented by general formula PF.

[0052] Further, the general formula P can be selected from at least one compound of the general formula PA, at least one compound of the general formula PF;

[0053] Further, the general formula P can be selected from at least one compound of the general formula PB, at least one compound of the general formula PF;

[0054] Further, the general formula P can be selected from at least one compound of the general formula PD, at least one compound of the general formula PF;

[0055] Furthermore, the general formula P can be selected from at least one compound of the general formula PG and at least one compound of the general formula PF.

[0056] Further preferably, the compound represented by the general formula P is selected from one or more of the compound groups represented by structural formulas P-1 to P-50:

[0057]

[0058]

[0059]

[0060]

[0061] In some embodiments of the present invention, the weight percentage of the compound represented by the general formula P in the liquid crystal composition is 0.001%-5%, and the specific content is, for example, 0.005%, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, etc.; preferably, the weight percentage of the compound represented by the general formula P in the liquid crystal composition is 0.01%-2%; further preferably, the weight percentage of the compound of the general formula P in the liquid crystal composition is 0.25%-0.35%.

[0062] In some embodiments of the present invention, the compound represented by general formula II is preferably selected from the compounds represented by the following formulae II-A to II-H:

[0063]

[0064] Among them, R C1 , R C2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms.

[0065] Furthermore, the compound represented by general formula II is selected from a combination of compounds represented by any two or more of general formulae II-A, II-B, II-C, II-D and II-F.

[0066] Further, the general formula II may be selected from at least one compound of the general formula II-A and at least one compound of the general formula II-B;

[0067] Further, the general formula II may be selected from at least one compound of the general formula II-A and at least one compound of the general formula II-D;

[0068] Further, the general formula II may be selected from at least one compound of the general formula II-B and at least one compound of the general formula II-C;

[0069] Further, Formula II may be selected from at least one compound of Formula II-B and at least one compound of Formula II-D;

[0070] Further, the general formula II can be selected from at least one compound of the general formula II-B and at least one compound of the general formula II-D, at least one compound of the general formula F;

[0071] Further, the general formula II can be selected from at least one compound of the general formula II-A, at least one compound of the general formula II-C, and at least one compound of the general formula D;

[0072] Further, the general formula II may be selected from at least one compound of the general formula II-B, at least one compound of the general formula II-C, and at least one compound of the general formula D;

[0073] Furthermore, the general formula II can be selected from at least one compound of the general formula II-A, at least one compound of the general formula II-B, at least one compound of the general formula C, and at least one compound of II-D.

[0074] In some embodiments of the present invention, preferably, the compound of formula II is one or more compounds selected from the group consisting of the following compounds II-1 to II-68:

[0075]

[0076]

[0077]

[0078] Relative to the total weight of the liquid crystal composition of the present invention, the weight percentage of the compound of formula II is 1%-60%, preferably 1%-58%, 1%-56%, 1%-50%, 1%-48%, 1%-45%, 2%-60%, 2%-50%, 2%-48%, etc.; relative to the total weight of the liquid crystal composition of the present invention, the lower limit of the weight percentage of the compound of formula II is 1%, 1.5%, 2%, 3%, 4%, 5% %, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 20%, 22%, 24% or 26%; the upper limit of the weight percentage of the compound of formula II is 60%, 58%, 56%, 54%, 52%, 50%, 48%, 45%, 40%, 38%, 35%, 30%, 28%, 26%, 24%, 20%, 18%, 16%, 15%, 14%, 12% or 10%.

[0079] In some embodiments of the present invention, preferably, the compound represented by the general formula III is one or more compounds selected from the group consisting of the following compounds III-1 to III-18:

[0080]

[0081] Relative to the total weight of the liquid crystal composition of the present invention, the weight percentage of the compound represented by the general formula III is 1%-60%, preferably 1%-58%, 1%-56%, 1%-50%, 1%-48%, 1%-45%, 2%-60%, 2%-50%, 2%-48%, etc.; the lower limit of the weight percentage of the compound represented by the general formula III is 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80 ... %, 12%, 14%, 16%, 20%, 22%, 24% or 26%; relative to the total weight of the liquid crystal composition of the present invention, the upper limit of the weight percentage of the compound of formula III is 60%, 58%, 56%, 54%, 52%, 50%, 48%, 45%, 40%, 38%, 35%, 30%, 28%, 26%, 24%, 20%, 18%, 16%, 15%, 14%, 12% or 10%.

[0082] In some embodiments of the present invention, the compound represented by the general formula M is selected from one or more of compounds MA to ML:

[0083]

[0084] Furthermore, the compound represented by the general formula M is selected from a combination of any two, three or more compounds represented by the general formulae MA, MB, MC, MD, ME, MF and MJ.

[0085] Further, the general formula M can be selected from at least one compound of the general formula MB, at least one compound of the general formula MC and at least one compound of MJ;

[0086] Further, the general formula M can be selected from at least one compound of the general formula MA, at least one compound of the general formula MC, at least one compound of MF, at least one compound of MJ;

[0087] Further, the general formula M can be selected from at least one compound of the general formula MA, at least one compound of MC, and at least one compound of the general formula MJ;

[0088] Further, the general formula M can be selected from at least one compound of the general formula MC, at least one compound of the general formula ME;

[0089] Further, the general formula M can be selected from at least one compound of the general formula MB, at least one compound of the general formula MC, at least one compound of MD, at least one compound of ME;

[0090] Further, the general formula M can be selected from at least one compound of the general formula MC, at least one compound of the general formula MD, and at least one compound of MJ;

[0091] Further, the general formula M can be selected from at least one compound of the general formula MC, at least one compound of the general formula MD;

[0092] Furthermore, the general formula M can be selected from at least one compound of the general formula MA, at least one compound of the general formula MB, at least one compound of MC, and at least one compound of MJ.

[0093] Preferably, the compound represented by the general formula M is selected from one or more of the following compounds M-1 to M-96:

[0094]

[0095]

[0096]

[0097]

[0098]

[0099] Relative to the total weight of the liquid crystal composition of the present invention, the weight percentage of the compound of general formula M is 1%-70%, preferably 1%-68%, 1%-65%, 1%-60%, 1%-50%, 2%-70%, 2%-60%, etc.; the lower limit of the weight percentage of the compound of general formula M is 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 20%, 22%, 24% or 26%; relative to the total weight of the liquid crystal composition of the present invention, the upper limit of the weight percentage of the compound of general formula M is 70%, 68%, 65%, 60%, 50%, 48%, 45%, 40%, 38%, 35%, 30%, 28%, 26%, 24%, 20%, 18%, 16%, 15%, 14%, 12% or 10%.

[0100] The liquid crystal composition of the present invention may further include one or more compounds having a structure represented by general formula IV:

[0101]

[0102] Among them, R G1 , R G2 Each independently represents C1-C 12 Alkyl or C1-C 12 Alkoxy, wherein C1-C 12 Alkyl or C1-C 12At least one hydrogen atom in the alkoxy group of C1-C 12 Alkyl or C1-C 12 One -CH2- or at least two non-adjacent -CH2- in the alkoxy group may be independently substituted by -O-, -CH=CH-, -C≡C-, -CO-O- or -O-CO- in a non-directly connected manner;

[0103] X1 and X2 each independently represent -F or -CF3.

[0104] In some embodiments of the present invention, the compound represented by the general formula IV is selected from one or more of the following compounds IV-1 to IV-40:

[0105]

[0106]

[0107]

[0108] In some embodiments of the present invention, the compound of general formula IV accounts for 0.1-20% of the total weight of the liquid crystal composition. Preferably, the compound of general formula IV accounts for 1-20% or 3-20% of the total weight of the liquid crystal composition. The specific content is, for example, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, etc.

[0109] The liquid crystal composition of the present invention may further include one or more compounds represented by general formula V:

[0110]

[0111] Among them, R 51 , R 52 Each independently represents C1-C 12 Alkyl or C1-C 12 Alkoxy; wherein C1-C 12 Alkyl or C1-C 12 At least one hydrogen atom in the alkoxy group of C1-C 12 Alkyl or C1-C 12 One -CH2- or at least two non-adjacent -CH2- in the alkoxy group may be independently substituted by -O-, -CH=CH-, -C≡C-, -CO-O- or -O-CO- in a non-directly connected manner;

[0112] Rings E1 and E2 are independent of each other.

[0113] Z 51 represents -CH2CH2-, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CO-O-, -C2F4-, or -CF=CF-;

[0114] q represents 0 or 1.

[0115] Furthermore, the compound represented by general formula V is selected from one or more of the following groups consisting of compounds V-1 to V-7:

[0116]

[0117] In some embodiments of the present invention, the compound represented by general formula V accounts for 0.1-20% of the total weight of the liquid crystal composition. Preferably, the compound represented by general formula V accounts for 1-20% or 3-20% of the total weight of the liquid crystal composition. The specific content is, for example, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, etc.

[0118] On the other hand, the polymerizable liquid crystal composition provided by the present invention further comprises one or more additives known to those skilled in the art and described in the literature, such as a stabilizer.

[0119] For example, one or more stabilizers having the following structures may be added to the liquid crystal mixture of the present invention:

[0120]

[0121]

[0122]

[0123] Preferably, the stabilizer is selected from one or more stabilizers having the following structures:

[0124]

[0125] In the stabilizer, n represents a positive integer of 1-12, for example, 1, 2, 3, 4, 5, 6, 8, 10 or 11, etc. Specific examples are as follows:

[0126]

[0127] In an embodiment of the present invention, the stabilizer accounts for 0-5% of the total weight of the liquid crystal composition; preferably, the stabilizer accounts for 0-1% of the total weight of the liquid crystal composition; more preferably, the stabilizer accounts for 0.01-0.2% of the total weight of the liquid crystal composition.

[0128] The liquid crystal composition of the present invention may further contain one or more additives known to those skilled in the art and described in the literature, for example, 0-15% of a pleochroic dye and / or a chiral dopant may be added.

[0129] The following are possible dopants which are preferably added to the liquid-crystal mixtures according to the invention:

[0130]

[0131]

[0132] In the embodiment of the present invention, the dopant preferably accounts for 0-5% of the total weight of the liquid crystal composition; more preferably, the dopant accounts for 0-1% of the total weight of the liquid crystal composition.

[0133] The use of the negative polymerizable liquid crystal composition of the present invention in the preparation of liquid crystal display devices can be used to prepare liquid crystal display devices comprising the negative liquid crystal composition of the present invention, preferably in VA, MVA, PVA, PSVA and other VA type liquid crystal display devices and / or IPS, FFS mode liquid crystal display devices, more preferably in MVA, PVA, PSVA mode liquid crystal displays, and further preferably in PSVA mode liquid crystal displays.

[0134] Advantages of the present invention:

[0135] The compound used in the present invention has stable chemical and physical properties, good low-temperature mutual solubility, low rotational viscosity, large elastic constant, moderate dielectric anisotropy and refractive index anisotropy, and has wide applicability.

[0136] The negative liquid crystal composition of the present invention has good low-temperature mutual solubility, large elastic constant, shortened response time, good high-temperature reliability, stable pretilt angle and low RM residue.

[0137] During UV light irradiation, the RM polymerization in the liquid crystal mixture of the present invention is controllable, the pretilt angle formed is uniform, and can be stably maintained under high and low temperature conditions. At the same time, the RM residue after polymerization should be as small as possible. In addition, this type of liquid crystal composition should have suitable optical anisotropy, suitable dielectric, low rotational viscosity, and good low-temperature storage performance to achieve the purpose of reducing the response time.

[0138] The liquid crystal composition of the present invention has very low rotational viscosity, good phase properties and good low-temperature properties, can form a lower pre-tilt angle after UV irradiation, has less RM residue, lower threshold voltage and faster response time, and the formed pre-tilt angle can be kept stable for a long time under high and low temperature conditions. The liquid crystal composition of the present invention can meet the requirements of liquid crystal display devices for low power consumption and good display effects, and has high application value in VA mode, MVA mode and PVA mode, especially PSVA type liquid crystal displays. DETAILED DESCRIPTION

[0139] For ease of expression, in the following embodiments, the group structures of the liquid crystal compositions are represented by the codes listed in Table 1.

[0140] Table 1 Group structure codes of liquid crystal compounds

[0141]

[0142]

[0143] Take the following compound as an example:

[0144]

[0145] In the code shown in Table 1, it is 3CPWO2, 3 represents cyclohexyl, C represents cyclohexane, P represents -1,4-diphenyl, W represents 2,3-difluorobenzene, and 4 represents butyl.

[0146] Another example:

[0147]

[0148] The code in Table 1 is 4CC1OWC3.

[0149] The abbreviated codes for the test items in the following embodiments are as follows:

[0150] Cp (℃): clearing point (nematic-isotropic phase transition temperature);

[0151] Δn: refractive index anisotropy (589nm, 25℃);

[0152] Δε: Dielectric anisotropy (1KHz, 25°C); where Δε = ε || -ε ⊥ , where ε || is the dielectric constant parallel to the molecular axis, ε ⊥ is the dielectric constant perpendicular to the molecular axis, test conditions: 25°C, 1KHz;

[0153] t(ms): response time (25±0.5℃); Liquid crystal is filled between two glass substrates and measured by LCT-5016. The gap between the glass substrates is 3.5μm;

[0154] t=t on +t off :t on It represents the time required for the relative transmittance to change from 10% to 90%, t off It indicates the time required for the relative transmittance to change from 90% to 10%;

[0155] γ1: represents the rotational viscosity [mPa·s] measured at 25°C, which is measured by the rotation method in a magnetic field;

[0156] LTS: Low temperature storage stability, the liquid crystal mixture is stored in a glass bottle under low temperature conditions.

[0157] K11: splay elastic constant;

[0158] K33: bending elastic constant;

[0159] VHR: Voltage holding ratio. Liquid crystal is filled between two glass substrates and measured with TOYO LCM-2. The higher the voltage holding ratio, the fewer mobile ions in the liquid crystal display component, and the better the stability of the liquid crystal display component.

[0160] Pretilt angle: refers to the angle between the long axis of the liquid crystal molecules and the surface of the glass substrate. For VA display mode, the liquid crystal molecules are initially close to being perpendicular to the surface of the glass substrate, that is, they have a pretilt angle of 90°. The value of the pretilt angle is measured by the OPTIRO pretilt angle tester.

[0161] Comparative Example 1: A mixture D1 was prepared according to the compounds and weight percentages listed in Table 2, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture D1 are shown in Table 2 below.

[0162] Table 2 Composition (weight %) and properties of mixture D1

[0163]

[0164]

[0165] Example 1: A mixture M1 was prepared according to the compounds and weight percentages listed in Table 3, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M1 are shown in Table 3 below.

[0166] Table 3 Composition (weight %) and properties of mixture M1

[0167]

[0168] Comparative Example 2: A mixture D2 was prepared according to the compounds and weight percentages listed in Table 4, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture D2 are shown in Table 4 below.

[0169] Table 4 Composition (weight %) and properties of mixture D2

[0170]

[0171] Example 2: A mixture M2 was prepared according to the compounds and weight percentages listed in Table 5, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M2 are shown in Table 4 below.

[0172] Table 5 Composition (weight %) and properties of mixture M2

[0173]

[0174]

[0175] Comparative Example 3: A mixture D3 was prepared according to the compounds and weight percentages listed in Table 6, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture D3 are shown in Table 6 below.

[0176] Table 6 Composition (weight %) and properties of mixture D3

[0177]

[0178] Example 3: A mixture M3 was prepared according to the compounds and weight percentages listed in Table 7, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M3 are shown in Table 6 below.

[0179] Table 7 Composition (weight %) and properties of mixture M3

[0180]

[0181] Comparative Example 4: A mixture D4 was prepared according to the compounds and weight percentages listed in Table 8, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture D4 are shown in Table 8 below.

[0182] Table 8 Composition (weight %) and properties of mixture D4

[0183]

[0184] Example 4: A mixture M4 was prepared according to the compounds and weight percentages listed in Table 9, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M4 are shown in Table 9 below.

[0185] Table 9 Composition (weight %) and properties of mixture M4

[0186]

[0187] Example 5: A mixture M5 was prepared according to the compounds and weight percentages listed in Table 10, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M5 are shown in Table 10 below.

[0188] Table 10 Composition (weight %) and properties of mixture M5

[0189]

[0190]

[0191] Example 6: A mixture M6 was prepared according to the compounds and weight percentages listed in Table 11, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M6 are shown in Table 11 below.

[0192] Table 11 Composition (weight %) and properties of mixture M6

[0193]

[0194] Example 7: A mixture M7 was prepared according to the compounds and weight percentages listed in Table 12, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M7 are shown in Table 12 below.

[0195] Table 12 Composition (weight %) and properties of mixture M7

[0196]

[0197] Example 8: A mixture M8 was prepared according to the compounds and weight percentages listed in Table 13, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M8 are shown in Table 13 below.

[0198] Table 13 Composition (weight %) and properties of mixture M8

[0199]

[0200]

[0201] Example 9: A mixture M9 was prepared according to the compounds and weight percentages listed in Table 14, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M9 are shown in Table 14 below.

[0202] Table 14 Composition (weight %) and properties of mixture M9

[0203]

[0204] Example 10: A mixture M10 was prepared according to the compounds and weight percentages listed in Table 15, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M10 are shown in Table 15 below.

[0205] Table 15 Composition (weight %) and properties of mixture M10

[0206]

[0207] Example 11: A mixture M11 was prepared according to the compounds and weight percentages listed in Table 16, and filled between two substrates of a liquid crystal display for performance testing. The composition and test data of the mixture M11 are shown in Table 16 below.

[0208] Table 16 Composition (weight %) and properties of mixture M11

[0209]

[0210] Example 12: 300 ppm of the following additives were added to the mixture of D1-D4 and M1-M11:

[0211]

[0212] Use UV (313nm 5.5mw / cm 2 ) for two minutes under an applied voltage of 20 V, and then UV (313 nm 0.5 mw / cm 2 ) for 85 min, and the pretilt angle, threshold voltage, response time, RM residue and voltage holding ratio (VHR 5V, 6Hz, 60°C) were tested respectively. The test results are shown in Table 17.

[0213] Table 17 Test performance of liquid crystal composition

[0214]

[0215]

[0216] Pretilt angle stability test: select several pieces from the above test box, age them at 60°C, backlight, for 300 hours, test the pretilt angle, and evaluate the pretilt angle stability. The results are shown in Table 18.

[0217] Table 18 Pretilt Angle Stability Test

[0218] Comparative Example UV rear pretilt angle° 300h / ° Pretilt angle change after 300h / ° D1 88.6 88.1 0.5 D2 88.1 87.4 0.7 D3 88.4 87.7 0.7 D4 88.2 87.4 0.8 M1 88.3 88.1 0.2 M2 88.4 88.2 0.2 M3 88.3 88.1 0.2 M4 88.7 88.5 0.1 M5 88.2 88.0 0.2 M6 88.8 87.7 0.1 M7 88.5 88.4 0.2 M8 88.4 88.3 0.2 M9 88.6 88.4 0.1 M10 88.4 88.2 0.2 M11 88.5 88.4 0.1

[0219] Several pieces from the above test box were selected and aged at -20°C for 300 hours to test the pretilt angle and evaluate the pretilt angle stability. The results are shown in Table 19:

[0220] Table 19 Pretilt Angle Stability Test

[0221] Comparative Example UV rear pretilt angle° 300h / ° Pretilt angle change after 300h / ° D1 88.4 88.0 0.5 D2 88.2 87.6 0.6 D3 88.3 87.7 0.6 D4 88.3 87.6 0.7 M1 88.5 88.3 0.2 M2 88.4 88.3 0.1 M3 88.4 88.2 0.2 M4 88.6 88.5 0.1 M5 88.4 88.2 0.2 M6 88.8 87.7 0.1 M7 88.4 88.2 0.2 M8 88.4 88.2 0.2 M9 88.5 88.4 0.1 M10 88.5 88.3 0.2 M11 88.6 88.5 0.1

[0222] It can be seen from the above application comparative examples and embodiments that the liquid crystal composition of the present invention has a very low rotational viscosity, good phase performance and good low-temperature performance, can form a lower pre-tilt angle after UV irradiation, has less RM residue, lower threshold voltage and faster response time, and the formed pre-tilt angle can be kept stable for a long time under high and low temperature conditions. The liquid crystal composition of the present invention can meet the requirements of liquid crystal display devices for low power consumption and good display effects, and has a high application value in VA mode, MVA mode and PVA mode, especially PSVA type liquid crystal displays.

Claims

1. A polymerizable liquid crystal composition, characterized in that: Contains at least one compound represented by the general formula IA or the general formula IB: Among them, R A1 , R A2 Each independently represents an alkyl group having 1 to 12 carbon atoms or an alkenyl group having 2 to 12 carbon atoms; At least one compound represented by the general formula P: Among them, rings B1, B2, and B3 are independently represented in One or more H on the molecule can be replaced by -F, -Cl, or -OCH3; Z 4、 Z5 each independently represents a CC single bond, -CH2CH2-, -CH=CH-, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CO-O-, -C2F4-, or -CF=CF-; P1 and P2 each independently represent a methacrylate group or an acrylate group; Sp1 and Sp2 each independently represent a spacer group or a CC single bond; the spacer group is a straight or branched alkyl chain group of 1 to 6 carbon atoms; r and s each independently represent an integer from 0 to 4; At least one compound of formula II: Among them, R C1 , R C2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms; Rings C1, C2, and C3 are each independently low At least one of and At most one H on can be replaced by F; c represents 0, 1, 2. When c represents 2, the ring C2 may be the same or different; d represents 0 or 1; At least one compound of formula III: Where R D1 , R D2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms; and at least one compound represented by the general formula M, wherein the compound M is selected from the compounds represented by the general formula MI and / or M-II: Among them, R M1 , R M2 Each independently represents an alkyl group having 1 to 12 carbon atoms or an alkoxy group having 1 to 12 carbon atoms; Rings M1 and M2 are represented independently Calculated by mass percentage, the content of the compound represented by general formula IA or general formula IB is 1-50%, the content of the compound represented by general formula P is 0.001-5%, the content of the compound represented by general formula II is 1-50%, the content of the compound represented by general formula III is 1-50%, and the weight percentage of the compound represented by general formula M is 1%-70%.

2. The polymerizable liquid crystal composition according to claim 1, characterized in that: The compound represented by the general formula P is selected from one or more of the group consisting of compounds PA to PK: Wherein, P1 and P2 each independently represent a methacrylate group or an acrylate group; Sp represents a spacer group or a single bond; and the spacer group is a straight or branched alkyl chain group of 1 to 6 carbon atoms.

3. The polymerizable liquid crystal composition according to claim 1, characterized in that: The compound represented by general formula II is selected from the compounds represented by general formula II-A to II-H: Among them, R C1 , R C2 Each independently represents an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, or an alkenyl group having 2 to 12 carbon atoms.

4. The polymerizable liquid crystal composition according to claim 1, characterized in that: The compound represented by the general formula M is selected from one or more of compounds MA to ML: Among them, R M1 , R M2 Each independently represents an alkyl group having 1 to 12 carbon atoms or an alkoxy group having 1 to 12 carbon atoms.

5. The polymerizable liquid crystal composition according to any one of claims 1 to 4, characterized in that: The polymerizable liquid crystal composition further comprises one or more compounds having a structure represented by general formula IV: Among them, R G1 , R G2 Each independently represents C1-C 12 Alkyl or C1-C 12 Alkoxy, C1-C 12 Alkyl or C1-C 12 At least one hydrogen atom in the alkoxy group of C1-C 12 Alkyl or C1-C 12 One -CH2- or at least two non-adjacent -CH2- in the alkoxy group may be independently substituted by -O-, -CH=CH-, -C≡C-, -CO-O- or -O-CO- in a non-directly connected manner; X1 and X2 each independently represent -F or -CF3; The compound of formula IV accounts for 1-20% of the total weight of the liquid crystal composition.

6. The polymerizable liquid crystal composition according to claim 5, characterized in that: The polymerizable liquid crystal composition further comprises one or more compounds represented by general formula V: Among them, R 51 , R 52 Each independently represents C1-C 12 Alkyl or C1-C 12 Alkoxy; C1-C 12 Alkyl or C1-C 12 At least one hydrogen atom in the alkoxy group of C1-C 12 Alkyl or C1-C 12 One -CH2- or at least two non-adjacent -CH2- in the alkoxy group may be independently substituted by -O-, -CH=CH-, -C≡C-, -CO-O- or -O-CO- in a non-directly connected manner; Rings E1 and E2 are independent of each other. Z 51 represents -CH2CH2-, -CF2O-, -OCF2-, -CH2O-, -OCH2-, -CO-O-, -C2F4-, or -CF=CF-; q represents 0 or 1; The compound represented by general formula V accounts for 1-20% of the total weight of the liquid crystal composition.

7. The polymerizable liquid crystal composition according to claim 6, characterized in that: The liquid crystal mixture further comprises one or more stabilizers and / or one or more chiral dopants. The content of the stabilizer is 0-5%, and the content of the chiral dopant accounts for 0-15% by mass of the entire liquid crystal composition.

8. A liquid crystal display device, characterized in that: The invention comprises the polymerizable liquid crystal composition according to any one of claims 1 to 7, wherein the liquid crystal display device comprises VA, MVA, PVA, PSVA, IPS and FFS mode liquid crystal display devices.

Citation Information

Patent Citations

  • Liquid crystalline compound, liquid crystal composition, and liquid crystal display element

    CN101827805A

  • Tetracyclic liquid crystalline compound having lateral fluorine, liquid crystal composition and liquid crystal display element

    CN102056881A